Recontextualisation of biodiversity knowledge in the Senior Phase Natural Sciences curriculum - Mmekwa, Makwena (Rhodes University, Faculty of Education, Department of Education, 2019)
This study explored the nature of biodiversity knowledge in the Senior Phase Natural Sciences curriculum in relation to international and national scientific documents. Significant biodiversity key features were identified from a review of these documents. These concepts were then explored in terms of how they had been presented and recontextualised in the Senior Phase Natural Sciences CAPS policy document and a selection of three commonly used textbooks for this subject in South Africa. Using Bernstein's (1990) framework of the Pedagogic Device, the study traces how biodiversity knowledge was de-located from the scientific Field of Production (FOP) and relocated into the Official Recontextualisation Field (ORF) and Pedagogical Recontextualisation Field (PRF). In exploring the continuity, changes and discontinuities in the biodiversity content, as it has been recontextualised, the study utilised Bernstein's concepts of selective appropriation and ideological transformation. The study is a qualitative case study that drew on document analysis and structured interviews to generate data. Data analysis for this study consisted of two phases. Phase One involved an analysis of biodiversity knowledge in the Millennium Ecosystem Assessment (MEA, 2005) and Life: The State of South Africa's Biodiversity (SANBI, 2013) which represented the FOP. This was in order to explore the nature of biodiversity knowledge in those documents. This knowledge was then compared to the Senior Phase Natural Sciences curriculum which represented the ORF and selection of textbooks representing the PRF. Phase Two sought to investigate the role players in the recontextualising fields and what roles did they play in the recontextualisation of biodiversity knowledge. This phase entailed an analysis of interviews. The findings showed that both the international document and the national document presented biodiversity knowledge in terms of their fundamental value to humans. In addition, these documents illustrated human-environmental interactions. They presented procedural knowledge that allow us to understand ecosystems and their services to human well-being. The documents also described how ecosystem services are in decline in many places around the world. The documents presented knowledge of threats to biodiversity such as habitat loss, invasive species, pollution, and overharvesting. They also included knowledge of conservation and sustainability which focused on preventing ongoing degradation and restoration and reversal of degradation of ecosystems. In comparing the ORF and the PRF this study showed that the CAPS policy document appears to present concepts foundational to understanding biodiversity rather than discussing biodiversity itself. The textbooks contextualise these foundational concepts and broaden them mostly through pictorial illustrations, as case studies and contextual examples. A recommendation from the research is that the official recontextualisation process should review opportunities to draw on international and national documents that present concepts and contemporary cases of biodiversity content knowledge to ensure that the complexities around biodiversity are presented in the curriculum. This study may contribute to the development and review of the Natural Sciences curriculum and environmental education in South Africa. The study also suggests areas of biodiversity knowledge that might be included as curriculum content in the future. It further suggests that curriculum developers consider including new environmental knowledge which deals with local, national and global needs and expectations.
Keywords: Science -- Study and teaching (Secondary) -- South Africa; Biodiversity -- Study and teaching (Secondary) -- South Africa; Environmental protection -- South Africa; Biodiversity Conservation -- South Africa; Millennium Ecosystem Assessment (Program); South African National Biodiversity Institute. Life: the state of -- South Africa's biodiversity